Implementing the Sustainable Development Goals (SDG) through course assessment activities / Mohd Idham Mohd Yusof ... [et al.] - Mohd Yusof, Mohd Idham; Ab Rahman, Farah Adilla; Yusof, Radduan; Kassim, Asiyah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Sustainable Development Goals (SDG) are the global agenda of the United Nations (UN) to achieve economic, social, and environmental sustainability through the concerted effort of multiple stakeholders. The 2030 global agenda, as the continuation of the Local Agenda 21 (LA21) and the Millennium Development Goals (MDG), calls for a worldwide, national, and institutional transformation towards a better world, emphasising sustainability as the primary objective. Supported by 17 goals, 169 targets and 247 indicators, the SDG, whose deadline is 2030, is viewed as an ambitious and complex idea towards achieving a realistic condition of sustainability. Nevertheless, the SDG is seen as relevant to bring out changes at various levels of governance and institutions towards sustainability commitment. SDG implementation at the higher educational institution is vital as it provides sustainability knowledge to the learners, aiming to produce future sustainability leaders and nurture sustainable practices at the university level. For example, the Faculty of Administrative Science and Policy Studies (FSPPP) has offered sustainable development-related academic courses for UiTM. Nearly all of its undergraduate and postgraduate programmes offer courses that embed sustainable development elements or specifically on the SDG. For example, EVA630 (Sustainable Development Strategies), which is provided to Bachelor of Environmental Administration (AM226) students, and PAD350 (Fundamentals of Sustainable Development), which is offered to Diploma in Public Administration students, are among the relevant courses for SDG. In fact, during the curriculum review, a mapping with SDG elements is necessary to ensure that these courses are aligned with the global agenda.